2006
DOI: 10.1634/stemcells.2005-0117
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation Restores the Antioxidative Capacity and Prevents Cell Damage in Bone Marrow Stromal Cells In Vitro

Abstract: STEM CELLS 2006;24: 1226 -1235

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 72 publications
8
112
0
2
Order By: Relevance
“…Similarly as in our study, 48-hour-exposure to selenium nanoparticles showed no significant influence on SOD in intestinal epithelial cells of crucian carp [22]. On the other hand, treatment with 100 nM sodium selenite caused increase in SOD activity in telomerase-immortalized human mesenchymal stem cell line [18]. In another interesting study the comparison of three different forms of selenium (methylseleninic acid, methylselenocysteine and Se yeast) was performed on ERpositive MCF-7 and triple-negative MDA-MB 231 human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly as in our study, 48-hour-exposure to selenium nanoparticles showed no significant influence on SOD in intestinal epithelial cells of crucian carp [22]. On the other hand, treatment with 100 nM sodium selenite caused increase in SOD activity in telomerase-immortalized human mesenchymal stem cell line [18]. In another interesting study the comparison of three different forms of selenium (methylseleninic acid, methylselenocysteine and Se yeast) was performed on ERpositive MCF-7 and triple-negative MDA-MB 231 human breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…Sodium selenite (1μM in the culture media, 11 days) significantly enhanced GPx in human hepatoma Hep G2 cells [17]. Sodium selenite (100 nM) supplementation caused significant increase in GPx activity in bone marrow stromal cells as well as in telometase-immortalized human mesenchymal stem cell line [18]. According to Barayuga et al sodium selenite (10 or 100 nM for a week) was found to increase GPx1 and GPx4 isoforms in SH-SY5Y neuronal cells in dose-dependent way [5].…”
Section: Discussionmentioning
confidence: 97%
“…Chronic treatment of N-acetyl cysteine or supplementation with selenium can reduce senescence markers through reduction of ROS levels [35,36]. APE1/Ref-1 can also decrease intracellular ROS levels [16].…”
Section: Overexpression Of Ape1/ref-1 Decreases Superoxide Generationmentioning
confidence: 99%
“…Selenium, as sodium selenite, has been reported as a co-factor for glutathione peroxidase and other proteins and used as an anti-oxidant in medium (Wu et al 1973). In cell culture system, sodium selenite protected cell from oxidative damage, free radicals and obstructed lipid perioxide products (Ebert et al 2006). Transferrin and Selenium played a role in the antioxidant defense system in the oocyte, which was essential for the catalytic activity of glutathione peroxidase (Cerri et al 2009).…”
Section: Discussionmentioning
confidence: 99%